2003
DOI: 10.1590/s0036-36342003000900015
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting utilization of cervical cancer prevention services in low-resource settings

Abstract: ResumenLas estrategias para introducir o fortalecer programas de prevención de cáncer cervical deben enfocarse hacia garantizar servicios costo-efectivos, que se encuentren disponibles para que las mujeres que los necesiten puedan utilizarlos. Este artículo resume la experiencia de proyectos de investigación realizados en Bolivia, Perú, Kenya, Sudáfrica y México. Los factores que afectan la tasa de participación en programas de prevención son categorizados en tres secciones. La primera describe los factores qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
139
0
20

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(168 citation statements)
references
References 11 publications
9
139
0
20
Order By: Relevance
“…Rates were much higher where clinics were more accessible or where mobile clinics brought services to women. 16,17 In our study, women with no health insurance coverage, and those who were not using contraceptive methods, were also less likely to have been screened. This profile was basically the same whether the women had not been screened in the previous two years or had never been screened.…”
Section: Findings and Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Rates were much higher where clinics were more accessible or where mobile clinics brought services to women. 16,17 In our study, women with no health insurance coverage, and those who were not using contraceptive methods, were also less likely to have been screened. This profile was basically the same whether the women had not been screened in the previous two years or had never been screened.…”
Section: Findings and Discussionmentioning
confidence: 66%
“…Studies that have analysed other barriers to Pap smear screening showed that waiting times, availability of counselling and arrangements to assure maximum privacy during the examination are important determinants of women's uptake of Pap tests. 16,17 Thus, assuring the availability of women-centred, high quality services is essential to high coverage.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…They also do not realize that cervical cancer can be treated in its early stages and they may surrender to a sense of fatalism. Similar attitudes and beliefs are common obstacles to screening and treatments in other countries (Bingham et al, 2003). Kaders, community advocacy teams, and television advertising were able to raise awareness, increase knowledge, and prompt many women to go for VIA screening.…”
Section: Discussionmentioning
confidence: 81%
“…In many cultures, the notion of preventing an illness years in the future may not be valued within the household. 37 Potential socio-cultural barriers to seeking care include embarrassment about the pelvic examination, fear of the procedure or of being associated with sexually transmitted infections, or fear of learning they have cancer. Women may also mistrust health care providers, either because they have been treated badly by them in the past or because they have heard of poor treatment from others.…”
Section: Service Availabilitymentioning
confidence: 99%
“…It is also possible to overcome the effects of negative local images of cervical cancer as a death sentence, or of a positive screening test as a sign of marital infidelity, by careful messaging in educational materials and interactions. 37 As with other clinical services, ensuring that women are treated with respect and that services are perceived to be of good quality is an important determinant of women's willingness to take up screening and encourage others to do so. 51 Offering HPV vaccine to young adolescent girls…”
Section: Making Screening and Pre-cancer Treatment Accessiblementioning
confidence: 99%